Interfacial Fracture Energy Between New Translucent Zirconias and a Resin Cement - Nadal, Laura Patricia Ortiz [UNESP]; de Carvalho Ramos, Nathália; Tribst, João Paulo Mendes; Anami, Lilian Costa [UNESP]; de Melo, Renata Marques [UNESP]; Bottinof, Marco Antonio [UNESP] (My University, 2022)
Purpose: To determine the interfacial fracture energy (IFE) and stress distribution of Brazil-nut–shaped specimens made of translucent zirconia and resin cement Materials and Methods: Three types of translucent zirconia were used: 3Y-TZP (high, Vita YZ HT), 4Y-TZP (super, Vita YZ ST), and 5Y-TZP (extra, Vita YZ XT). The adhesive surfaces were air abraded and 10-MDP-based resin ce ment was used. The cemented Brazil-nut–shaped specimens, with an elliptical defect in the center (as in real Brazil nuts), were thermally aged (5°C–55°C; 40,000 cycles). The IFE test was conducted with a piston to apply compres sion on the specimen, while the adhesive interface was positioned at four different angles (0, 10, 20, and 30 de grees) to measure the IFE during tensile, shear, and mixed failure modes. All adhesive interfaces were observed to determine failure patterns. The finite element analysis (FEA) was used to calculate tensile and shear stress distri butions according to inclinations. Statistical analysis was conducted using the Kruskal-Wallis and Dunn’s post-hoc tests (95%), as well as the Mann-Whitney test (95%) was applied to compare each group regarding the aging factor. Results According to Kruskal-Wallis and Dunn’s post-hoc tests, there were no statistically significant differences be tween non-aged (p>0.05) and aged materials (p>0.05). However, there was a significant difference between aged and non-aged materials for all inclinations (p<0.05) (Mann-Whitney test). According to the FEA, the compressive loading of Brazil-nut–shaped specimens at different angles showed a predominance of tensile stress at 0 degrees and shear stress at 30 degrees. Conclusion The IFE under predominantly shear stresses is higher than when specimens are subjected only to ten sile stresses, which allows the interpretation that failures in the oral environmental will probably occur preferen tially under tensile stresses, because less energy is needed. All translucent zirconia bonded to resin cement has similar IFE, and thermal aging negatively affects these bonding interfaces.
Keywords: Dental materials; Finite element analysis; Fracture; Zirconia